Evolutionary Study of Watershed Governance Research: A Bibliometric Analysis. Issue 4 (2nd October 2021) - Widianingsih, Ida; Paskarina, Caroline; Riswanda, Riswanda; Putera, Prakoso Bhairawa
ABSTRACT: This study aims to analyze scientific literatures on watershed governance from the first published paper (1979) to the present (2020) through bibliometric analysis and visualization by utilizing a VOS-viewer software based on Scopus database. This study retrieved 353 articles from international authors focusing on watershed governance topic that are related to rural-urban linkages, and local government capacity. The articles are classified according to year of publication, author, the country of co-authors, affiliation, keywords, and journal title. Furthermore, the articles are examined based on several indicators including: Contribution of Countries/Institutions/Authors, Distribution of Journals, Highly Cited Articles, Bibliographic Coupling, and Keywords Analysis. The United States, Canada, and the United Kingdom are the leading countries contributing to publications on watershed governance topic from 1979 to 2020. McGill University serves as the most productive institution, followed by Ohio State University and University of British Columbia. Meanwhile, in terms of disciplines, Public Administration and Development, Environment and Urbanization, and Public Policy and Administration are the top three published journals. The combination of bibliographies and keyword concurrency networks indicates that the research topic of watershed governance is strongly associated to research topics such as rural-urban linkages and local government.